Winning in emerging markets a road map for strategy and execution - Krishna G. Palepu, Tarun Khanna (Boston Harvard Business Press, 2010)
Introduction -- The nature of institutional voids in emerging markets -- Spotting and responding to institutional voids -- Exploiting institutional voids as business opportunities -- Multinationals in emerging markets -- Emerging giants : competing at home -- Emerging giants : going global -- The emerging arena.
Includes bibliographical references and index.
Keywords: Commerce